Laboratory-derived inflammatory ratios as a novel diagnostic model for premature coronary artery disease - Guo, Fujia; Xu, Min; Tu, Qingxian; Yang, Heyun; Linghu, Keqiang; Li, Botao; Zhang, Jie; Luo, Ya; Huang, Hong (Frontiers in Endocrinology, 2025)
IntroductionCoronary artery disease (CAD) is showing a trend toward earlier onset. Premature CAD (PCAD) is clinically defined as CAD with onset before the age of 55 in males and 65 in females. Notably, many young patients subsequently hospitalized with acute cardiovascular events had undergone annual physical examinations before hospitalization, yet were not identified as high-risk by current risk stratification guidelines or traditional risk assessment tools. This study aims to investigate the diagnostic capacity of novel inflammatory biomarkers (including the monocyte-to-high-density lipoprotein cholesterol ratio (MHR), platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), apolipoprotein B to apolipoprotein A-1 ratio (apoB/apoA-1), and low-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (LDL-c/HDL-c)) for PCAD, thereby providing the evidence-based foundation for PCAD screening.MethodsA total of 1,012 young subjects (male<55 years, female<65 years) undergoing diagnostic coronary angiography (CAG) at the Third Affiliated Hospital of Zunyi Medical University (from January 2022 to February 2023) were retrospectively analyzed. We stratified 1,012 eligible participants into two groups: 521 angiographically confirmed PCAD cases and 491 controls with normal coronary arteries. Comprehensive baseline characteristics, including cardiovascular risk profiles and core laboratory-measured inflammatory markers, were recorded. The Mann-Whitney U test and binary logistic regression analysis were employed to assess the associations between inflammatory biomarkers and PCAD. The areas under the receiver operating characteristic (ROC) curves (AUCs) were calculated to evaluate their diagnostic performance for PCAD.ResultsThe odds ratio (OR) values for MHR, NLR, LDL-c/HDL-c, and apoB/apoA-1 were 5.592 (95% CI: 2.886-7.836), 1.671 (95% CI: 1.500-1.861), 1.663 (95% CI: 1.419-1.950), and 6.268 (95% CI: 2.765-8.213), respectively (all P < 0.001). LMR was not identified as an independent risk factor for PCAD. After adjusting for confounding factors, apoB/apoA-1 remained the strongest risk factor for PCAD compared to other inflammatory markers. The AUCs for MHR, NLR, LDL-c/HDL-c, and apoB/apoA-1 were 0.621 (95% CI: 0.587-0.656), 0.735 (95% CI: 0.703-0.766), 0.605 (95% CI: 0.570-0.640), and 0.771 (95% CI: 0.742-0.799), respectively (all P < 0.001). Furthermore, the diagnostic model combining apoB/apoA-1 with neutrophil, lymphocyte, monocyte, triglyceride, uric acid, HDL-c, age, sex, smoking, alcohol consumption, diabetes mellitus, and family history of hypertension, diabetes mellitus, and CAD achieved the highest AUC of 0.898 (95% CI: 0.880-0.917). We analyzed the diagnostic value of inflammatory markers for acute coronary syndrome (ACS) in PCAD patients. The AUCs for these four inflammatory markers were 0.661 (95% CI: 0.626-0.696) for MHR, 0.726 (95% CI: 0.692-0.760) for NLR, 0.615 (95% CI: 0.579-0.651) for LDL-c/HDL-c, and 0.795 (95% CI: 0.766-0.824) for apoB/apoA-1 (all P < 0.001), indicating that apoB/apoA-1 had higher diagnostic value for ACS in PCAD than other inflammatory markers. Additionally, the combined diagnostic model incorporating apoB/apoA-1 with the aforementioned covariates achieved an AUC of 0.923 (95% CI: 0.906-0.940) for ACS.ConclusionsThe apoB/apoA-1 outperformed MHR, NLR, and LDL-c/HDL-c as an inflammatory biomarker in PCAD. Its diagnostic capacity was notably enhanced in ACS subgroups. A comprehensive model combining apoB/apoA-1 with traditional risk factors demonstrated exceptional accuracy. Incorporating this biomarker into routine screening protocols could significantly strengthen preventive strategies.